Syringa reticulata subsp. amurensis growth influencing the microbial diversity and heavy metal contents in mixed substrate of municipal sludge and construction waste. Issue 1 (31st December 2022) - Liu, Xueya; Liu, Lijuan; Leng, Pingsheng; Hu, Zenghui
ABSTRACT: The municipal sludge and construction waste can be used in cultivating substrate for plants, but the effect of plant growth on the microbial diversity and heavy metal contents is largely unknown. In this study, municipal sludge and construction waste residue were mixed to cultivate Syringa reticulata subsp. amurensis . After sowing seeds on the mixed substrate, the microbial diversity and heavy metal contents of the substrate were measured after 3-month and 7-month growth of S. reticulata subsp. amurensis . The results showed that S. reticulata subsp. amurensis seedlings grew well in the mixed substrate. Moreover, the substrate revealed a different microbial diversity. The relative abundance of the top microbial phylum, Proteobacteria, decreased with the plant growth, as well as Bacteroidetes and Actinobacteria. Gemmatimonadetes presented increasing relative abundance. In addition, the heavy metal contents decreased with plant growth, suggesting that S. reticulata subsp. amurensis removed heavy metals from the mixed substrate.